Description of Pharmaceutical Services and Levels of Patient Satisfaction with Services at Two Pharmacies in Lahat District - Reza Agung Sriwijaya; Novi Nurleni; Isa Bella (Asian Journal of Healthcare Analytics, 2022)
A pharmacy is a place of pharmaceutical practice carried out by pharmacists in pharmaceutical services. 73 of 2016. This type of research is a descriptive quantitative observation of documents and a direct observation of pharmaceutical services in a coherent manner. instrument checklist form and patient satisfaction questionnaire. Overview of services at the Aliifah pharmacy the presence of a pharmacist is more than 5 hours/per day serving 200 doctor's prescriptions per month and in the Mubarak pharmacy, the presence of a pharmacist is less than 5 hours/per day with a total of 150 doctor's prescriptions per month. Pharmacy services at the Aliifah and Mubarok pharmacies are in the less category, while the level of satisfaction with the Aliifah and Mubarok pharmacy services is equally very satisfactory.